2005
DOI: 10.1002/marc.200500271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Helix‐Coil Diblock Copolymers with Controlled Supramolecular Architectures in Aqueous Solution

Abstract: Summary: A series of helix‐coil diblock copolymers based on poly(ethylene oxide) and optically active helical poly{(+)‐2,5‐bis[4′‐((S)‐2‐methylbutoxy)phenyl]styrene} (PMBPS) were synthesized via atom transfer radical polymerization (ATRP). The synthetic methodology permitted straightforward preparation of the diblock copolymers with relatively low polydispersities and a broad range of compositions and molecular weights. Depending on the composing block length and the initial concentration, the copolymers self‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…The specific optical rotation [a] , in THF) of MBPS was þ60.58; yet the two copolymers showed negative values of [a] 25 365 as MBPS homopolymer (Table 1). [20,21] The opposite sign of the copolymers to MBPS and the increase in magnitude suggested that the optical activity of the copolymer did not simply arise from the asymmetric centers within the side groups and that a higher structure, most likely a secondary helical conformation for a vinyl polymer such as PMBPS, was formed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The specific optical rotation [a] , in THF) of MBPS was þ60.58; yet the two copolymers showed negative values of [a] 25 365 as MBPS homopolymer (Table 1). [20,21] The opposite sign of the copolymers to MBPS and the increase in magnitude suggested that the optical activity of the copolymer did not simply arise from the asymmetric centers within the side groups and that a higher structure, most likely a secondary helical conformation for a vinyl polymer such as PMBPS, was formed.…”
Section: Resultsmentioning
confidence: 99%
“…The similar tendency has also been found in the system of helix-coil block copolymers. [20] In the present study, the initial copolymer concentrations varied from H. Cao, W. Lin, A. Liu, J. Zhang, X. Wan, Q. Zhou 0.005 to 1.0 wt.-%. However, no discernible changes in the morphology, size, and polydispersity of the aggregates with concentration were found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The helical conformation of the polypeptide and polyisocyanate is due to the intramolecular hydrogen bonding, chiral center in the repeat units, and/or short range restriction of rotation. [22][23][24][25][26][27][28] The rigidity of these polymers arises from the close wrapping of the side-on mesogens around the flexible backbone, forcing the latter to extend to form a supramolecular rod. An important class of mesogen-bearing block copolymers is those containing mesogen-jacketed liquid crystalline polymers (MJLCPs), [19][20][21] which were synthesized mostly through controlled/"living" radical polymerizations of designed monomers with laterally attached mesogenic side groups.…”
Section: Introductionmentioning
confidence: 99%